(untitled) (Experimental biology, 2020)
In model tests carried out in a greenhouse on apple trees, it was shown that in conditions of high infection pressure of E. amylovora, the one-off, preventive use of Aliette 80WG during full bloom was effective in reducing blossom blight in the range of 60-70%. There was no significant increase in efficacy after using this product twice in comparison to single application. However, Aliette turned out to be ineffective in the protection of terminal shoots. High efficacy, both in protecting blossoms and apple shoots, was shown by a cooper-based formulation Miedzian 50WP, but it caused some phytotoxicity on flower petals. Also in the test on slices of pear fruitlets, this product caused significant ressetting. Overall, the highest efficacy among the different formulations and bacterial isolates tested was recorded when the pear fruitlet slices were treated with the bacterial isolate A15 (Pantoea agglomerans) (96%); other effective products were the antibiotic-based Kasumin 2L (94%) and Miedzian 50WP (89%). It is noteworthy that Controlphyt Cu, a foliar and soil fertilizer containing Cu, showed quite high efficacy – up to 71% when applied at the concentration of 0.4% and 41% at 0.2%. Key words: fosetyl aluminium, copper, kasugamycin, biocontrol, apple, pear.